Konsumsi Literatur Keislaman Generasi Milenial Kabupaten Pekalongan di Era Digital - Awali, Husni (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2024)
The purpose of this study is to describe what Islamic literature is the material for millennial consumption in the current digital era, as well as what media millennials use as a reference in accessing Islamic literature and the extent to which the current digital era affects the Islamic literature of the millennial generation in Pekalongan Regency. This type of research is qualitative research with a descriptive approach to examine phenomena related to the Consumption of Islamic Literature for the Millennial Generation of Pekalongan Regency in the Digital Era. The results of the study stated that the Digital Era has changed the order of life, ranging from changes in behavior, ways of thinking, and ways of getting information, including the needs of the millennial generation of Islamic literature, especially in the Pekalongan Regency. where the need for the holy Qur'an has shifted to digital form, as well as the digital era provides easy access to Islamic literature needs, Besides that, literature in the current digital era makes millennials pampered with shows towards popular Islamic literature such as Islamic novels and study content from influencer figures who emigrated and become current role models. so that social media is now the most popular media channel for millennials in accessing various information, including information about Islam such as Instagram, TikTok, and Youtube, which are the most widely accessed platforms for millennials in Pekalongan Regency in fulfilling their Islamic literature needs.